Effect of structural modifications on the drying kinetics of foods: changes in volume, surface area and product shape - de Michelis, Antonio (2013)
Macro and micro-structural changes take place during food dehydration. Macro-structural changes encompass modifications in shape, area and volume. Studies of such changes are important because dehydration kinetics (essential for calculating industrial dryers) may be highly influenced by changes in food shape and dimensions. The overall changes in volume, surface area (?shrinkage?) and shape (Heywood factor, with provides a close description of food shape) were determined experimentally, and the results were correlated with simple expressions. Hence, although dehydration kinetics can be modeled with simplified overall shrinkage expressions, the possibility of selecting a suitable geometry and predicting the characteristics dimensions will provide higher accuracy. An additional unresolved problem is the lack of a general model that predicts macro-structural changes for various foods and diverse geometries. In this work, based on experimental data of sweet and sour cherries, and rose hip fruits, a simplified general model to predict changes in volume and surface area are proposed. To estimate how the changes in characteristic dimensions affect the kinetic studies, experimental drying curves for the three fruits by means of a diffusional model considered the following variants for the characteristic dimensions: (i) The radius of the fresh food, assumed constant; (ii) The radius of the partially dehydrated product; (iii) The radius predicted by the correlation for structural changes, especially volume, obtained in this work and generalized for the three fruits, and (iv) to demonstrate the need to study the macro-structural changes for all dehydrated foods, also be present the case of a restructured food.